Celibat duchownych – normy prawne, jego motywacje i praktyka w Kościele galijskim od połowy IV do połowy VI w. w świetle kanonów synodów kościelnych - Kołosowski, Tadeusz (Vox Patrum, 2020)
In the beginning, the ancient Church understood celibacy as a state of being unmarried of one’s own free-will. Once, married men were admitted to the clerical state. From the mid-third century, unmarried men who were ordained, could not marry. From the fourth century, the formal law of celibacy was introduced prescribing a total sexual abstinence in relations with one’s wife. These legal norms were confirmed by numerous synods in Gaul to ensure their observance. Abstinence under celibacy is motivated mainly by a cult continence, the teaching of the Gospel and that of St. Paul the Apostle. Non-observance was sanctioned by different penalties, especially removal from the office and excommunication.